# Solve this equation using the quadratic formula: (2x-3)^2 - 14 = 2x(x-7)

### 1 Answer | Add Yours

First, we need to simpify the equation to standard form `(ax^2+bx+c)` :

Expand the squared term:

`(2x-3)(2x-3)-14=2x(x-7)`

Next expand the multiplication:

`4x^2-6x-6x+9-14=2x^2-14x`

Finally, move all terms to the left side and collect like terms:

`4x^2-2x^2-12x+14x-5=0`

`2x^2+2x-5=0`

We can now solve for the roots of this equation using the quadratic formula:

`x=(-b+-sqrt(b^2-4ac)) /(2a)`

a=2; b=2; c=-5

`x=(-2+-sqrt(2^2-4(2)(-5))) /(2(2))`

`x=(-2+-sqrt(44))/4`

`x_1=(-2+sqrt(44))/4 =1.16`

`x_2=(-2-sqrt(44))/4=-2.16`

Graph of the function: